This is a local museum, for local natural history specialist groups - Simmons, Z; Jarvis, C (Natural Sciences Collections Association, 2018)
With more people taking part in biological recording, surveying, and joining natural history societies than ever, how and why should museums work with these groups? Although there is overlap in interests, these societies often either do not engage with museums or, at worst, have a mistrust of them. In 2011, the Oxford University Museum of Natural History held a symposium for specialist interest groups in Oxfordshire and, ever since, has worked to build trust, engage more deeply with this audience, and cultivate mutually beneficial relationships. This paper summarises the findings from this symposium and other research into what natural history specialist interest groups and museums can offer each other to grow each organisation, deepen links, promote collaboration, and create both wider and more impactful participation in natural history events. We will describe our findings of what specialist interest groups feel is best practice from museums, a selection of different methods of collaborating with specialist interest groups, and how our museum has developed its model of engagement to build a strong local network of those engaged with natural history but not natural history museums.